Anthropology as critique: The legacy of Joel Kahn. (September 2019) - Baldacchino, Jean-Paul; Houston, Christopher
Joel S. Kahn (1946–2017), was one of the founding editors of Critique of Anthropology. Throughout his career Joel continually adhered to an anthropology founded on the praxis of critique. Through his fieldwork in South East Asia and his own incursions into Western modernity and modernist thought, Joel was committed to a form of anthropology that challenged strict disciplinary conventions. The papers in this special issue written by his colleagues and students engage with some of the important themes he developed in his work rendering tribute to his ongoing legacy for generations of anthropologists.